Pengaruh Edukasi Berbasis Video Terhadap Tingkat Pengetahuan Ibu tentang Gizi Seimbang bagi Balita di Desa Tanjung Sari Lampung Timur - Probowati, Endang; Selasih Putri Isnawati Hadi; Eka Vicky Yulivantina (Journal of Midwifery Science: Basic and Applied Research, 2025)
Toddlerhood, especially during the first 1,000 days of life, is a critical phase for growth and development. Balanced nutrition during this period greatly determines children’s future health and development. Mothers play a central role in fulfilling children’s nutritional needs; therefore, effective education methods are required. This study aimed to examine the effect of video-based education on mothers’ knowledge of balanced nutrition for toddlers. The population consisted of all mothers of toddlers in Tanjung Sari Village, East Lampung. The sample was 64 mothers selected using total sampling. A pre-experimental design with one-group pretest-posttest was applied. Data were collected using a structured questionnaire before and after a 5-minute educational video, which was screened twice. Data analysis used a paired t-test to determine knowledge differences before and after the intervention. Results showed a significant improvement in mothers’ knowledge after the intervention (mean difference = 15.07; p < 0.001). Video-based education effectively increases mothers’ knowledge of balanced nutrition for toddlers. This medium is recommended for healthcare workers and posyandu cadres as an engaging, efficient, and easy-to-understand educational tool.